Positive electrode for all-solid-state battery and all-solid-state battery including the same
The positive electrode for all-solid-state batteries, featuring a bromine-containing and bromine-free sulfide-based solid electrolytes, addresses conductivity and interfacial issues, enhancing ionic conductivity and charge/discharge performance.
Patent Information
- Application Number
- JP2024529665
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-11-07
- Filing Date
- 2023-08-25
- Publication Date
- 2024-12-26
- Estimated Expiration
- 2043-08-25
AI Technical Summary
Existing all-solid-state batteries using sulfide-based solid electrolytes face issues with ionic conductivity and interfacial properties due to reactions between the positive electrode active material and the sulfide-based solid electrolyte, leading to decreased life characteristics and increased electrode resistance.
A positive electrode for all-solid-state batteries is developed, incorporating a sulfide-based solid electrolyte containing a bromine element in the coating layer and another sulfide-based solid electrolyte without bromine, which enhances the contact area and interfacial properties, improving ionic conductivity and electrode dispersibility.
The solution maintains flexible deformation characteristics during manufacturing, reduces interfacial resistance, and enhances ionic conductivity, resulting in improved charge/discharge capacity and high rate characteristics of the all-solid-state batteries.
Smart Images

Figure 2024546588000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0146682, filed November 7, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a positive electrode for an all-solid-state battery and an all-solid-state battery including the same. [Background technology]
[0003] Lithium secondary batteries have been mainly used in small areas such as mobile devices and laptops, but recently, research on them has expanded to medium and large areas such as energy storage systems (ESS) and electric vehicles (EV).
[0004] Unlike small batteries, medium and large lithium secondary batteries not only have harsh operating environments (e.g., temperature, impact), but also require the use of more batteries, so safety must be ensured along with excellent performance and reasonable prices.
[0005] Most lithium secondary batteries currently on the market use organic liquid electrolytes in which lithium salts are dissolved in flammable organic solvents, which poses the potential risk of leakage, fire, and explosion. As a result, the use of solid electrolytes instead of organic liquid electrolytes has been drawing attention as an alternative solution to overcome the safety issues.
[0006] All-solid-state batteries are composed of a positive electrode, a solid electrolyte, and a negative electrode. Sulfides and oxides can be used as the solid electrolyte for all-solid-state batteries, but sulfide-based solid electrolytes are the most promising material from the perspective of lithium ion conductivity.
[0007] However, when using a sulfide-based solid electrolyte, a positive electrode active material coated with cobalt (Co) is generally not used in the positive electrode due to the reaction between cobalt and sulfur.
[0008] In addition, during the charge / discharge cycle of an all-solid-state battery, reactions occur at the interface between the positive electrode active material and the sulfide-based solid electrolyte, causing components such as Co, P, and S to diffuse from the interface, resulting in reduced life characteristics, and this issue needs to be improved. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Korean Patent Publication No. 10-2010-0120153 (2010.11.12) [Patent Document 2] Korean Patent Publication No. 10-2018-0076132 (2018.07.05) Summary of the Invention [Problem to be solved by the invention]
[0010] An object of the present invention is to provide a positive electrode for an all-solid-state battery, which includes both a sulfide-based solid electrolyte containing bromine (Br) and a sulfide-based solid electrolyte not containing bromine, and which applies the sulfide-based solid electrolyte containing bromine to a coating layer of a positive electrode active material, thereby improving ion conductivity and interfacial characteristics between the active material and the solid electrolyte.
[0011] Another object of the present invention is to provide an all-solid-state battery having improved electrochemical characteristics and life characteristics by applying the all-solid-state battery positive electrode. [Means for solving the problem]
[0012] One embodiment of the present invention provides a positive electrode for an all-solid-state battery, the positive electrode comprising a positive electrode active material, a sulfide-based solid electrolyte, a conductive material, and a binder, the sulfide-based solid electrolyte comprising a first sulfide-based solid electrolyte containing a bromine (Br) element and a second sulfide-based solid electrolyte not containing a bromine (Br) element, the positive electrode active material comprising a core capable of reversibly absorbing and releasing lithium ions; and a coating layer formed on a surface of the core, the coating layer comprising the first sulfide-based solid electrolyte.
[0013] The first sulfide-based solid electrolyte is represented by the following Chemical Formula 1.
[0014] [Chemical formula 1] Li a M 1 b S c X 1 d Br e
[0015] In the above Chemical Formula 1, M 1 is Sn, Mg, Ba, B, Al, Ga, In, In, Si, Ge, Pb, N, P, As, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W, or La; 1 is F, Cl, Br, I, Se, Te, or O, and 0 <a≦6、0<b≦6、0<c≦6、0≦d≦6および0<e≦6である。
[0016] The second sulfide-based solid electrolyte is represented by the following chemical formula 2.
[0017] [Chemical formula 2] Li k M 2 l S m X 2 n
[0018] In the above formula 2, M 2is Sn, Mg, Ba, B, Al, Ga, In, In, Si, Ge, Pb, N, P, As, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W, or La; 2 is F, Cl, I, Se, Te, or O, and 0 <k≦6、0<l≦6、0<m≦6および0≦n≦6である。
[0019] The sulfide-based solid electrolyte may have an Argyrodite-type crystal structure.
[0020] The first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte may be contained in a weight ratio of 95:5 to 5:95.
[0021] The positive electrode active material may be included in an amount of 50 to 95 parts by weight based on 100 parts by weight of the total positive electrode.
[0022] The sulfide-based solid electrolyte may be included in an amount of 5 to 49 parts by weight based on 100 parts by weight of the total positive electrode.
[0023] The positive electrode active material may be coated with 1 to 20 parts by weight of a first sulfide-based solid electrolyte based on 100 parts by weight of the total positive electrode active material including the core and the coating layer.
[0024] The first sulfide-based solid electrolyte has an average particle size of 0.1 to 5 μm.
[0025] The second sulfide-based solid electrolyte has an average particle size of 0.1 to 5 μm.
[0026] Another embodiment of the present invention is a positive electrode; negative electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode; The positive electrode includes the positive electrode for the all-solid-state battery. Effect of the Invention
[0027] According to the present invention, a positive electrode for an all-solid-state battery includes a positive electrode active material and a sulfide-based solid electrolyte, and the sulfide-based solid electrolyte includes a first sulfide-based solid electrolyte including a bromine (Br) element and a second sulfide-based solid electrolyte not including a bromine element, and the first sulfide-based solid electrolyte is applied to a coating layer of the positive electrode active material, thereby maintaining flexible deformation characteristics during a pressurizing process during the manufacture of the all-solid-state battery, and exhibiting excellent interfacial characteristics as a result of an increased contact area between the positive electrode active material and the solid electrolyte. In addition, the positive electrode for the all-solid-state battery includes the second sulfide-based solid electrolyte not including a bromine element, thereby increasing the dispersibility of the positive electrode and improving the resistance of the electrode, thereby improving the ionic conductivity of the all-solid-state battery. [Brief description of the drawings]
[0028] [Figure 1] 1 and 2 show scanning electron microscope (SEM) images of a cross section of a positive electrode for an all-solid-state battery according to one embodiment of the present invention. [Diagram 2] 1 and 2 show scanning electron microscope (SEM) images of a cross section of a positive electrode for an all-solid-state battery according to one embodiment of the present invention. [Diagram 3] FIG. 3 shows a transmission electron microscope (TEM) image of a cross section of a positive electrode for an all-solid-state battery according to one embodiment of the present invention. [Figure 4] FIG. 4 shows an analysis result of Energy Dispersive X-ray Spectroscopy (EDS) of a cross section of a positive electrode for an all-solid-state battery according to an embodiment of the present invention. [Diagram 5] FIG. 5 shows the voltage change depending on the cost amount in the all-solid-state batteries according to the examples of the present invention and the comparative examples. [Figure 6] FIG. 6 shows high rate characteristics in the all-solid-state batteries according to the examples of the present invention and the comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Hereinafter, the embodiments of the present invention will be described in detail. Prior to this, the terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as having meanings and concepts that are consistent with the technical idea of the present invention, based on the principle that the inventor can appropriately define the concept of the term to best describe his / her invention. Therefore, since the configurations described in the embodiments described in this specification are merely the most preferred embodiment of the present invention and do not represent the entire technical idea of the present invention, it should be understood that there are various equivalents and modifications that can replace them at the time of this application.
[0030] Throughout this specification, when a part is said to "comprise" a certain element, this means that it can further include other elements, rather than excluding other elements, unless specifically stated to the contrary.
[0031] Throughout this specification, the average particle size of particles may be the median diameter (D50) measured, for example, using a laser particle size analyzer.
[0032] Hereinafter, a positive electrode for an all-solid-state battery according to one embodiment of the present invention will be described.
[0033] The present invention relates to a positive electrode for an all-solid-state battery, which has improved ionic conductivity and improved interfacial characteristics between a positive electrode active material and a solid electrolyte in the positive electrode for the all-solid-state battery.
[0034] Generally, all-solid-state batteries differ from typical lithium secondary batteries in that they do not use a liquid electrolyte, and therefore contain a solid electrolyte not only in the solid electrolyte layer but also in the positive electrode active material layer.
[0035] At this time, in order to ensure stable ion conductivity, it is important for the positive electrode active material contained in the positive electrode active material layer to come into effective contact with the solid electrolyte to form a high effective contact area, which acts as an important factor in improving the charge / discharge capacity and efficiency of the all-solid-state battery. In order to increase the effective contact area between the positive electrode active material and the solid electrolyte, a pressure of about 500 MPa or more is applied during the manufacturing process of the all-solid-state battery, and in order to solve the problems caused by the pressure process, there have been attempts to improve this by introducing a coating layer of solid electrolyte to the positive electrode active material.
[0036] However, when a coating layer is introduced to the positive electrode active material as described above, the effective contact area between the positive electrode active material and the solid electrolyte increases, thereby reducing the resistance of the electrode, but the contact between the solid electrolyte formed in the coating layer of the positive electrode active material and the solid electrolyte present in the positive electrode active material layer, which is not formed in the coating layer, decreases, which may cause a problem of a decrease in the ionic conductivity of the battery. In addition, when the positive electrode is manufactured by coating the entire positive electrode active material with a solid electrolyte, voids are generated in the positive electrode active material layer, which may ultimately reduce the ionic conductivity and charge / discharge efficiency of the battery.
[0037] In order to solve the above problems, the present invention provides a positive electrode for an all-solid-state battery comprising a positive electrode and a sulfide-based solid electrolyte, the sulfide-based solid electrolyte comprising both 1) a first sulfide-based solid electrolyte containing bromine (Br) and 2) a second sulfide-based solid electrolyte not containing bromine, the first sulfide-based solid electrolyte being included in a coating layer of a positive electrode active material, thereby enabling flexible deformation characteristics to be maintained during a pressurizing process during the manufacture of an all-solid-state battery, and as a result of an increased contact area between the positive electrode active material and the solid electrolyte, excellent interfacial characteristics are exhibited, the dispersibility of the positive electrode is increased, and the resistance of the electrode is improved, thereby improving ion conductivity and charge / discharge capacity, thereby completing the present invention.
[0038] 1 and 2 show SEM images of a cross section of a positive electrode for an all-solid-state battery according to one embodiment of the present invention.
[0039] Referring to FIGS. 1 and 2, a positive electrode for an all-solid-state battery according to an embodiment of the present invention includes a positive electrode active material, a sulfide-based solid electrolyte, a conductive material, and a binder. The sulfide-based solid electrolyte includes a first sulfide-based solid electrolyte containing a bromine (Br) element and a second sulfide-based solid electrolyte not containing a bromine (Br) element. The positive electrode active material includes a core capable of reversibly absorbing and releasing lithium ions; and a coating layer formed on a surface of the core, and the coating layer includes the first sulfide-based solid electrolyte.
[0040] The positive electrode for the all-solid-state battery simultaneously includes a first sulfide-based solid electrolyte containing bromine (Br) and a second sulfide-based solid electrolyte not containing bromine, and the first sulfide-based solid electrolyte is applied to a coating layer of a positive electrode active material, thereby maintaining flexible deformation characteristics during a pressurizing process during the manufacture of the all-solid-state battery, and exhibiting excellent interface characteristics as a result of an increased contact area between the positive electrode active material and the solid electrolyte. In addition, the positive electrode for the all-solid-state battery also includes the second sulfide-based solid electrolyte not containing bromine, thereby increasing the dispersibility of the positive electrode and improving the resistance of the electrode, thereby improving the ionic conductivity of the all-solid-state battery.
[0041] Without being limited to a particular theory, it can be understood that the first sulfide-based solid electrolyte contained in the positive electrode active material coating layer contains a bromine element, thereby forming a particular crystal structure, thereby suppressing side reactions at the interface between the positive electrode active material and the solid electrolyte. Therefore, when the sulfide-based solid electrolyte essentially containing bromine is coated on the surface of the positive electrode active material and applied to the positive electrode, it can reduce the interfacial resistance between the positive electrode active material and the solid electrolyte and increase the ionic conductivity.
[0042] In addition, the positive electrode for an all-solid-state battery according to the present invention includes a second sulfide-based solid electrolyte that does not contain bromine in addition to the first sulfide-based solid electrolyte that contains bromine. The second sulfide-based solid electrolyte exhibits excellent ductility against external pressure, and therefore maintains contact between the solid electrolytes even when the internal pressure increases during a pressurizing process in the manufacturing process of the all-solid-state battery or during the operation of the all-solid-state battery, thereby improving the ionic conductivity of the all-solid-state battery.
[0043] In one embodiment of the present invention, the first sulfide-based solid electrolyte may be represented by the following Chemical Formula 1:
[0044] [Chemical formula 1] Li a M 1 b S c X 1 d Br e
[0045] In the above formula 1, M 1 is Sn, Mg, Ba, B, Al, Ga, In, In, Si, Ge, Pb, N, P, As, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W or La; 1 is F, Cl, Br, I, Se, Te, or O, and 0 <a≦6、0<b≦6、0<c≦6、0≦d≦6および0<e≦6である。
[0046] For example, in the above Chemical Formula 1, M 1 may be B, Si, Ge, P or N.
[0047] For example, in the above Chemical Formula 1, X 1 may be F, Cl, Br, I or O.
[0048] For example, the first sulfide-based solid electrolyte represented by Chemical Formula 1 may be Li2S-P2S5-LiBr, Li2S-P2S5-LiCl-LiBr, Li2S-SiS2-LiBr, or a combination thereof.
[0049] In one embodiment of the present invention, the second sulfide-based solid electrolyte may be represented by the following Chemical Formula 2:
[0050] [Chemical formula 2] Li k M 2 l S m X 2 n
[0051] In the above formula 2, M 2 is Sn, Mg, Ba, B, Al, Ga, In, In, Si, Ge, Pb, N, P, As, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W or La; 2 is F, Cl, I, Se, Te or O, 0 <k≦6、0<l≦6、0<m≦6および0≦n≦6である。
[0052] For example, in the above formula 2, M 2 may be B, Si, Ge, P or N.
[0053] For example, in the above formula 2, X 2 may be F, Cl, I or O.
[0054] For example, the second sulfide-based solid electrolyte represented by Chemical Formula 2 may be Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-GeS2, Li2S-SiS2-Li3PO4, or a combination thereof.
[0055] In an embodiment of the present invention, the sulfide-based solid electrolyte, i.e., the first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte, may have an Argyrodite-type crystal structure.
[0056] Since the sulfide-based solid electrolyte has an argyrodite-type crystal structure, the sulfide-based solid electrolyte has high purity and crystallinity, and forms a stable interfacial phase, and can have a high energy density while significantly improving potential stability and ionic conductivity.
[0057] In an embodiment of the present invention, the first sulfide-based solid electrolyte may be included in an amount of 5 to 25 parts by weight based on 100 parts by weight of the first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte in total. For example, the first sulfide-based solid electrolyte may be included in an amount of 5 parts by weight or more, 6 parts by weight or more, 7 parts by weight or more, 8 parts by weight or more, 9 parts by weight or more, or 10 parts by weight or more based on 100 parts by weight of the first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte in total, or may be included in an amount of 25 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, 14 parts by weight or less, 13 parts by weight or less, 12 parts by weight or less, or 11 parts by weight or less. Preferably, the first sulfide-based solid electrolyte may be included in an amount of 7 to 10 parts by weight based on 100 parts by weight of the first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte in total.
[0058] In the positive electrode for an all-solid-state battery according to the present invention, if the content of the first sulfide-based solid electrolyte is less than 5 parts by weight based on 100 parts by weight of the first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte contained in the positive electrode for an all-solid-state battery, the content of the first sulfide-based solid electrolyte contained in the positive electrode active material coating layer is reduced, thereby reducing the effect of suppressing side reactions at the interface between the positive electrode active material and the solid electrolyte, and increasing the interfacial resistance between the positive electrode active material and the solid electrolyte, which may reduce the ion conductivity of the all-solid-state battery. If the content of the first sulfide-based solid electrolyte is more than 25 parts by weight based on 100 parts by weight of the first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte contained in the positive electrode for an all-solid-state battery, the thickness of the coating layer including the first sulfide-based solid electrolyte is excessively increased, and the positive electrode active material is isolated from the first sulfide-based solid electrolyte, which is a component of the coating layer, resulting in an increase in the resistance of the electrode.
[0059] In the positive electrode for an all-solid-state battery according to the present invention, if the content of the second sulfide-based solid electrolyte is less than 75 parts by weight based on 100 parts by weight of the total of the first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte contained in the positive electrode for an all-solid-state battery, there is a problem that voids are generated in the positive electrode active material layer, thereby reducing the ion conductivity of the electrode. On the other hand, if the content of the second sulfide-based solid electrolyte exceeds 95 parts by weight, the opposite problem may occur as when the content of the first sulfide-based solid electrolyte is less than 5 parts by weight.
[0060] Therefore, in order to improve the ionic conductivity and potential stability of the positive electrode for an all-solid-state battery according to the present invention and stably ensure the charge / discharge capacity and life characteristics of an all-solid-state battery including the positive electrode, the contents of the first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte are preferably adjusted within the above ranges.
[0061] In one embodiment of the present invention, the positive electrode active material may be included in an amount of 50 to 95 parts by weight based on 100 parts by weight of the total positive electrode. For example, the content of the positive electrode active material may be 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 75 parts by weight or more, or 80 parts by weight or more, or 95 parts by weight or less, 90 parts by weight or less, or 85 parts by weight or less, based on 100 parts by weight of the total positive electrode.
[0062] If the content of the positive electrode active material is less than 50 parts by weight based on 100 parts by weight of the total positive electrode, there is a problem of a decrease in the capacity and total energy density of the electrode, and if it exceeds 95 parts by weight, there is a problem of an increase in voids in the positive electrode active material layer, resulting in an increase in interfacial resistance between the positive electrode active material and the solid electrolyte. Therefore, in the case of the positive electrode for an all-solid-state battery according to the present invention, it is necessary to appropriately adjust the content of the positive electrode active material within the above range.
[0063] In one embodiment of the present invention, the sulfide-based solid electrolyte may be included in an amount of 5 to 49 parts by weight based on 100 parts by weight of the total positive electrode. The content of the sulfide-based solid electrolyte refers to the total content of the first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte included in the positive electrode, and may be, for example, 5 parts by weight or more, 6 parts by weight or more, 7 parts by weight or more, 8 parts by weight or more, 9 parts by weight or more, 10 parts by weight or more, 11 parts by weight or more, 12 parts by weight or more, 13 parts by weight or more, 14 parts by weight or more, 15 parts by weight or more based on 100 parts by weight of the total positive electrode, and may be 49 parts by weight or less, 45 parts by weight or less, 40 parts by weight or less, 35 parts by weight or less, 30 parts by weight or less, 25 parts by weight or less, 24 parts by weight or less, 23 parts by weight or less, 22 parts by weight or less, 21 parts by weight or less, or 20 parts by weight or less. Preferably, the sulfide-based solid electrolyte may be included in an amount of 12 to 20 parts by weight based on 100 parts by weight of the total positive electrode.
[0064] If the content of the sulfide-based solid electrolyte is less than 5 parts by weight based on 100 parts by weight of the total positive electrode, there is a problem that the number of voids in the positive electrode active material layer increases, and the interfacial resistance between the positive electrode active material and the solid electrolyte increases, resulting in a decrease in the capacity and total energy density of the electrode. If the content of the sulfide-based solid electrolyte is more than 49 parts by weight, there is a problem that the capacity and total energy density of the electrode decreases. Therefore, in the case of the positive electrode for an all-solid-state battery according to the present invention, it is necessary to appropriately adjust the total content of the sulfide-based solid electrolyte, i.e., the first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte, within the above range.
[0065] In an embodiment of the present invention, the positive electrode active material may be coated with 1 to 20 parts by weight of the first sulfide-based solid electrolyte based on 100 parts by weight of the total positive electrode active material including the core and the coating layer. For example, based on 100 parts by weight of the total positive electrode active material including the core and the coating layer, the positive electrode active material may be coated with 1 part by weight or more, 2 parts by weight or more, or 3 parts by weight or more, or 20 parts by weight or less, 15 parts by weight or less, 10 parts by weight or less, 9 parts by weight or less, 8 parts by weight or less, 7 parts by weight or less, 6 parts by weight or less, or 5 parts by weight or less.
[0066] In an embodiment of the present invention, the first sulfide-based solid electrolyte may have an average particle size of 0.1 to 5 μm. For example, the first sulfide-based solid electrolyte may have an average particle size of 0.1 to 3 μm, 0.1 to 2 μm, 0.1 to 1 μm, 0.1 to 0.9 μm, 0.1 to 0.8 μm, 0.1 to 0.7 μm, 0.1 to 0.6 μm, or 0.1 to 0.5 μm.
[0067] If the average particle size of the first sulfide-based solid electrolyte is less than 0.1 μm, the first sulfide-based solid electrolyte particles are easily scattered, which may cause a problem in that the formation of the coating layer does not proceed smoothly. If the average particle size of the first sulfide-based solid electrolyte is more than 5 μm, the thickness of the coating layer increases excessively, which may cause a problem in that the coating layer is not formed uniformly. Therefore, it is preferable that the first sulfide-based solid electrolyte of the positive electrode for an all-solid-state battery according to the present invention is appropriately adjusted to have an average particle size in the same range as above.
[0068] In one embodiment of the present invention, the second sulfide-based solid electrolyte may have an average particle size of 0.1 to 5 μm. For example, the second sulfide-based solid electrolyte may have an average particle size of 0.1 to 3 μm, 0.1 to 2 μm, 0.1 to 1 μm, 0.1 to 0.9 μm, 0.1 to 0.8 μm, or 0.2 to 0.8 μm.
[0069] If the average particle size of the second sulfide-based solid electrolyte is less than 0.1 μm, the second sulfide-based solid electrolyte particles may easily aggregate or not be uniformly dispersed, resulting in uneven concentration in the electrode, making it difficult to form an effective interface between the positive electrode active material and the second sulfide-based solid electrolyte. If the average particle size of the second sulfide-based solid electrolyte is more than 5 μm, voids may be generated in the positive electrode active material layer, resulting in a decrease in the ionic conductivity of the electrode. Therefore, it is preferable to appropriately adjust the average particle size of the second sulfide-based solid electrolyte of the positive electrode for an all-solid-state battery according to the present invention to be in the same range as above.
[0070] In one embodiment of the present invention, the coating layer formed on the surface of the positive active material may have a thickness of 0.05 to 0.2 μm. For example, the coating layer may have a thickness of 0.05 μm or more, 0.06 μm or more, 0.07 μm or more, 0.09 μm or more, or 0.1 μm or more, or 0.2 μm or less, 0.18 μm or less, 0.16 μm or less, or 0.15 μm or less.
[0071] If the thickness of the coating layer is less than 0.05 μm, the content of the first sulfide-based solid electrolyte that can be included in the positive electrode active material coating layer is reduced, the effect of suppressing side reactions at the interface between the positive electrode active material and the solid electrolyte is reduced, and the interfacial resistance between the positive electrode active material and the solid electrolyte is increased, which may reduce the ion conductivity of the all-solid-state battery.If the thickness of the coating layer is more than 0.2 μm, the positive electrode active material is isolated by the first sulfide-based solid electrolyte, which is a component of the coating layer, resulting in a problem of increased electrode resistance.
[0072] In an embodiment of the present invention, the positive electrode for the all-solid-state battery may further include a conductive material and a binder.
[0073] The conductive material is not particularly limited as long as it is conductive without causing a chemical change in the battery, and examples of the conductive material include graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fiber and metal fiber; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskey such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives. The conductive material may be included in an amount of about 0.01 to 10 parts by weight, or 0.01 to 5 parts by weight, or 0.01 to 3 parts by weight based on 100 parts by weight of the total positive electrode.
[0074] The binder is a component added in consideration of adhesion of a positive electrode active material, a sulfide-based solid electrolyte, and a conductive material to the positive electrode for the all-solid-state battery, and any polymer binder known to be usable for forming an electrode in the technical field to which the present invention belongs may be used without any particular limitation.
[0075] Examples of such polymer binders include acrylic binders, polyvinylidene fluoride (PVDF) binders, polytetrafluoroethylene (PTFE) binders, butadiene rubber binders such as nitrile butadiene rubber (NBR), and of course, various other polymer binders can be used. The binder can be included in an amount of about 0.01 to 10 parts by weight, or 0.01 to 5 parts by weight, or 0.01 to 3 parts by weight, based on 100 parts by weight of the total positive electrode.
[0076] A positive electrode for an all-solid-state battery according to an embodiment of the present invention may include a current collector and a positive electrode active material layer formed on at least one side of the current collector, and the positive electrode active material layer may include the positive electrode active material, a sulfide-based solid electrolyte, a conductive material, and a binder.
[0077] The positive electrode can be manufactured according to a method widely known in the art, and is not limited to a specific manufacturing method. For example, the positive electrode can be manufactured by mixing the positive electrode active material, a sulfide-based solid electrolyte, a conductive material, a binder, etc. in a solvent to manufacture a slurry-like positive electrode mixture, and applying the positive electrode mixture to a positive electrode current collector.
[0078] Meanwhile, the positive electrode active material is not particularly limited as long as it is a lithium composite oxide material capable of reversibly inserting and extracting lithium ions, for example, it may contain one or more composite oxides of metals such as cobalt, manganese, nickel, iron, or combinations thereof; and lithium.
[0079] More specifically, the positive electrode active material may be a compound represented by any one of the following chemical formulas: a A 1-b R b D2 (wherein, 0.90≦a≦1.8 and 0≦b≦0.5); Li a E 1-b R b O 2-c D c (wherein 0.90≦a≦1.8, 0≦b≦0.5, and 0≦c≦0.05); LiE 2-b R b O 4-c D c (In the above formula, 0≦b≦0.5, 0≦c≦0.05); Li a Ni 1-b-c Co b R c D α (In the above formula, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, 0<α≦2); Li a Ni 1-b-c Co b R c O 2-α Z α (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Co b Rc O 2-α Z2 (wherein 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b R c D α (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Mn b R c O 2-α Z2 (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b R c O 2-α Z2 (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni b E c G d O2 (wherein, 0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, and 0.001≦d≦0.1); Li a Ni b Co c Mn d G e O2 (wherein 0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, 0≦d≦0.5 and 0≦e≦0.1); Li a NiG b O2 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1); Li a CoG b O2 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1); Li a MnG b O2 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1); Li a Mn2G bO4 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiTO2; LiNiVO4; Li (3-f) J2(PO4)3(0≦f≦2); Li (3-f) Fe2(PO4)3(0≦f≦2); and LiFePO4.
[0080] In the above chemical formula, A is Ni, Co, Mn or a combination thereof; R is Al, Ni, Co, Mn, Cr, Fe, Fe, Mg, Mg, Sr, V, rare earth elements or a combination thereof; D is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; Z is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; T is Cr, V, Fe, Sc, Y or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu or a combination thereof.
[0081] The sulfide-based solid electrolyte is the same as that described above, and therefore, detailed description of the sulfide-based solid electrolyte contained in the positive electrode for an all-solid-state battery according to the present invention will be omitted in this specification.
[0082] The positive electrode current collector is generally 3 to 500 μm thick. Such a positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. The current collector can be formed with fine irregularities on its surface to increase the adhesive force of the positive electrode active material, and can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0083] In addition to the positive electrode active material, the sulfide-based solid electrolyte, the conductive material, and the binder, the positive electrode may further include additives such as a filler, a coating agent, a dispersant, an ion-conductive auxiliary, etc. As the filler, coating agent, dispersant, ion-conductive auxiliary, etc., known materials generally used in electrodes of all-solid-state secondary batteries may be used.
[0084] The thickness of the positive electrode may be, for example, 70 to 150 μm.
[0085] Another embodiment of the present invention provides an all-solid-state battery comprising a positive electrode, a negative electrode, and a solid electrolyte layer always disposed between the positive electrode and the negative electrode, the positive electrode being a positive electrode for the all-solid-state battery.
[0086] The positive electrode contained in the all-solid-state battery is as described above, so the negative electrode and solid electrolyte contained in the all-solid-state battery will be described in detail below.
[0087] The solid electrolyte layer disposed between the positive electrode and the negative electrode may include, for example, a sulfide-based solid electrolyte. The sulfide-based solid electrolyte may be the same or different from the sulfide-based solid electrolyte included in the positive electrode.
[0088] For specific details regarding the sulfide-based solid electrolyte, see the above-mentioned positive electrode section.
[0089] The elastic modulus of the solid electrolyte, i.e., Young's modulus, is, for example, 35 GPa or less, 30 GPa or less, 27 GPa or less, 25 GPa or less, or 23 GPa or less. The elastic modulus of the solid electrolyte, i.e., Young's modulus, is, for example, 10 to 35 GPa, 15 to 35 GPa, 15 to 30 GPa, or 15 to 25 GPa. When the solid electrolyte has an elastic modulus in this range, pressing and / or sintering of the solid electrolyte can be performed more easily.
[0090] The solid electrolyte layer further includes, for example, a binder. The binder included in the solid electrolyte layer is, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited thereto, and any binder used as a binder in the relevant technical field is possible. The binder of the solid electrolyte layer may be the same as or different from the binder of the positive electrode active material layer and the negative electrode active material layer.
[0091] Next, the negative electrode of the all-solid-state battery can include a negative electrode current collector and a negative electrode active material layer.
[0092] The thickness of the negative electrode active material layer is, for example, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less of the thickness of the positive electrode active material layer. The thickness of the negative electrode active material layer is, for example, 1 μm to 20 μm, 2 μm to 10 μm, or 3 μm to 7 μm. If the thickness of the negative electrode active material layer is too thin, lithium dendritic formed between the negative electrode active material layer and the negative electrode current collector collapses the negative electrode active material layer, making it difficult to improve the cycle characteristics of the all-solid-state battery. If the thickness of the negative electrode active material layer is excessively increased, the energy density of the all-solid-state battery decreases, the internal resistance of the all-solid-state battery due to the negative electrode active material layer increases, and the cycle characteristics of the all-solid-state battery are difficult to improve.
[0093] The negative electrode active material layer contains, for example, a negative electrode active material that forms an alloy or compound with lithium.
[0094] The negative electrode active material contained in the negative electrode active material layer has, for example, a particulate shape. The average particle size of the negative electrode active material having a particulate shape is, for example, 4 μm or less, 3 μm or less, 2 μm or less, 1 μm or less, or 900 nm or less. The average particle size of the negative electrode active material having a particulate shape is, for example, 10 nm to 4 μm or less, 10 nm to 3 μm or less, 10 nm to 2 μm or less, 10 nm to 1 μm or less, or 10 nm to 900 nm or less. When the negative electrode active material has an average particle size in this range, reversible absorbing and / or desorbing of lithium during charging and discharging becomes easier. The average particle size of the negative electrode active material is, for example, a volume-equivalent median diameter (D50) measured using a laser type particle size distribution meter.
[0095] The negative electrode active material contained in the negative electrode active material layer includes, for example, one or more selected from a carbon-based negative electrode active material and a metal or semi-metal negative electrode active material.
[0096] The carbon-based negative electrode active material is, in particular, amorphous carbon. Examples of amorphous carbon include, but are not limited to, carbon black (CB), acetylene black (AB), furnace black (FB), ketjen black (KB), graphene, etc., and any material classified as amorphous carbon in the art can be used. Amorphous carbon is carbon that has no crystallinity or has very low crystallinity, and is distinguished from crystalline carbon or graphite-based carbon.
[0097] The metal or semi-metallic negative electrode active material includes at least one selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn), but is not necessarily limited thereto, and may be any metal or semi-metallic negative electrode active material that forms an alloy or compound with lithium in the art. For example, nickel (Ni) does not form an alloy with lithium, and is therefore not a metal negative electrode active material.
[0098] The negative electrode active material layer includes one type of negative electrode active material among these negative electrode active materials, or includes a mixture of a plurality of different negative electrode active materials. For example, the negative electrode active material layer includes only amorphous carbon, or includes one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). In another embodiment, the negative electrode active material layer includes a mixture of amorphous carbon and one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). The weight ratio of the mixture of amorphous carbon and silver (Ag) is, for example, 10:1 to 1:2, 5:1 to 1:1, or 4:1 to 2:1, but is not necessarily limited to this range and is selected according to the required characteristics of the all-solid-state battery. When the positive electrode active material has such a composition, the cycle characteristics of the all-solid-state battery are further improved.
[0099] The negative electrode active material contained in the negative electrode active material layer includes, for example, a mixture of first particles made of amorphous carbon and second particles made of a metal or a metalloid. The metal or metalloid includes, for example, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). The metalloid is also a semiconductor. The content of the second particles is 8 to 60 wt%, 10 to 50 wt%, 15 to 40 wt%, or 20 to 30 wt%, based on the total weight of the mixture. When the second particles have a content in this range, for example, the cycle characteristics of the all-solid-state battery are further improved.
[0100] The negative electrode active material layer contains, for example, a binder. The binder is, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but is not necessarily limited thereto, and any binder used as a binder in the technical field is possible. The binder can be composed of a single binder or a plurality of different binders.
[0101] By including a binder in the negative electrode active material layer, the negative electrode active material layer is stabilized on the negative electrode current collector. In addition, cracks in the negative electrode active material layer are suppressed despite changes in volume and / or relative position of the negative electrode active material layer during charging and discharging. For example, when the negative electrode active material layer does not include a binder, the negative electrode active material layer can be easily separated from the negative electrode current collector. The portion where the negative electrode active material layer is separated from the negative electrode current collector is exposed and comes into contact with the solid electrolyte layer, which increases the possibility of short circuiting. The negative electrode active material layer is produced, for example, by applying a slurry in which materials constituting the negative electrode active material layer are dispersed onto the negative electrode current collector and drying it. By including a binder in the negative electrode active material layer, stable dispersion of the negative electrode active material in the slurry is possible. For example, when applying the slurry onto the negative electrode current collector by a screen printing method, clogging of the screen (for example, clogging due to agglomerates of the negative electrode active material) can be suppressed.
[0102] The negative electrode current collector is made of a material that does not react with lithium, i.e., does not form both an alloy and a compound. The material constituting the negative electrode current collector is, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co) and nickel (Ni), but is not necessarily limited thereto, and any material used as an electrode current collector in the technical field can be used. The negative electrode current collector may be made of one of the above metals, or may be made of an alloy or coating material of two or more metals. The negative electrode current collector is, for example, in the form of a plate or foil.
[0103] The positive electrode active material layer can further contain additives used in conventional all-solid-state batteries, such as a filler, a dispersant, an ion conductive agent, and the like.
[0104] An all-solid-state battery can be produced, for example, by producing a positive electrode, a negative electrode, and a solid electrolyte layer, and then laminating these layers.
[0105] The present invention provides a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0106] In this case, specific examples of the device include, but are not limited to, power tools that are driven by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.
[0107] Specific examples of the present invention are described below. However, the examples described below are merely for the purpose of specifically illustrating or explaining the present invention, and are not intended to limit the present invention. Furthermore, since the contents not described here can be fully inferred by those skilled in the art, the description thereof will be omitted.
[0108] Manufacturing Example 1: Manufacturing of positive electrodes for all-solid-state batteries (1) LiNi with a particle size (D50) of 5 μm as the positive electrode active material 0.8 Co 0.1 Mn 0.1 78 g of O2 powder and Li6PS5Cl with a particle size (D50) of 0.4 μm as the first sulfide-based solid electrolyte 0.5 Br 0.5 3.9 g of the powder was placed in a container and mixed for 1 minute at 5,000 rpm using a Lab Blender (Waring) without using a separate solvent (primary mixing).The mixture was then subjected to high shear mixing (NOB-130, Hosokawa Micron) at 3,000 rpm for 10 minutes to produce a cathode active material composite in which a first sulfide-based solid electrolyte coating layer was formed on the surface of the cathode active material.
[0109] (2) 81.9 parts by weight of the prepared positive electrode active material composite, 15.6 parts by weight of Li6PS5Cl as a second sulfide-based solid electrolyte, 1.5 parts by weight of carbon black powder as a conductive material, and 1 part by weight of polytetrafluoroethylene (PTFE) as a binder were put into a container and mixed at 5,000 rpm for 1 minute using a Lab Blender (Waring) without using a separate solvent (primary mixing). Next, a shear force of 100 N was applied to the mixture to perform high shear mixing (PBV-0.1L, Irie Shokai) to prepare a positive electrode slurry (secondary mixing).
[0110] (3) The prepared positive electrode slurry was processed into a free-standing film using a Two Roll Mill MR-3 (Inoue Co., Ltd.), and then the film was placed on one side of an aluminum current collector having a thickness of 15 μm and pressed to prepare a positive electrode for an all-solid-state battery.
[0111] Manufacturing Example 2: Manufacturing of positive electrodes for all-solid-state batteries In the process of manufacturing the positive electrode slurry, Li6PS5Cl was used instead of Li6PS5Cl as the second sulfide-based solid electrolyte. 0.5 Br 0.5 An all-solid-state battery was produced in the same manner as in Production Example 1, except that the above was used.
[0112] Manufacturing Example 3: Manufacturing of positive electrodes for all-solid-state batteries In the process of manufacturing the positive electrode active material composite, Li6PS5Cl was used as the first sulfide-based solid electrolyte. 0.5 Br 0.5 An all-solid-state battery was produced in the same manner as in Production Example 1, except that Li6PS5Cl was used instead of Li6PS5Cl.
[0113] Manufacturing Example 4: Manufacturing of positive electrodes for all-solid-state batteries In the process of manufacturing the positive electrode slurry, Li6PS5Cl was used as the first sulfide-based solid electrolyte. 0.5 Br 0.5 Instead of Li6PS5Cl, Li6PS5Cl was used as the second sulfide-based solid electrolyte.0.5 Br 0.5 An all-solid-state battery was produced in the same manner as in Production Example 1, except that the above was used.
[0114] Example 1: Fabrication of an all-solid-state battery A 100 μm thick lithium metal was used as the negative electrode, and a 50 μm thick Li2S-P2S5 solid electrolyte membrane was interposed between the positive electrode and the negative electrode prepared in Preparation Example 1. The battery had a capacity of 5 mAh / cm 2 We have manufactured a Jig Cell with a large capacity.
[0115] Comparative Example 1: Manufacturing of all-solid-state batteries An all-solid-state battery was produced in the same manner as in Example 1, except that the positive electrode produced in Production Example 2 was used instead of the positive electrode produced in Production Example 1.
[0116] Comparative Example 2: Manufacture of all-solid-state battery An all-solid-state battery was produced in the same manner as in Example 1, except that the positive electrode produced in Production Example 3 was used instead of the positive electrode produced in Production Example 1.
[0117] Comparative Example 3: Manufacture of all-solid-state battery An all-solid-state battery was produced in the same manner as in Example 1, except that the positive electrode produced in Production Example 4 was used instead of the positive electrode produced in Production Example 1.
[0118] Evaluation example 1: SEM and TEM analysis of positive electrodes for all-solid-state batteries The positive electrode for an all-solid-state battery prepared according to Preparation Example 1 was subjected to SEM (Scanning Electron Microscopy) analysis, and the results are shown in Figures 1 and 2. The SEM analysis was performed using a JEOL JEM-ARM200F microscope.
[0119] Referring to FIG. 1, in the case of the positive electrode for an all-solid-state battery prepared according to Preparation Example 1, it can be seen that a coating layer of a first sulfide-based solid electrolyte containing bromine is uniformly formed on the surface of the positive electrode active material.
[0120] In addition, referring to FIG. 2, in the case of the positive electrode for the all-solid-state battery prepared according to Preparation Example 1, it can be seen that the bromine-free second sulfide-based solid electrolyte is closely positioned between the positive electrode active material, and thus is in close contact with the positive electrode active material at the interface between the second sulfide-based solid electrolyte.
[0121] Evaluation example 2: TEM (Transmission electron microscopy) and EDX (Energy dispersive X-ray spectroscopy) analysis of positive electrodes for all-solid-state batteries (1) In order to determine whether a coating layer was formed on the positive electrode active material of the all-solid-state battery positive electrode prepared according to Preparation Example 1, a transmission electron microscopy (TEM) analysis was performed, and the results are shown in Figure 3. The TEM analysis was performed using FEI Titan G2 80-200.
[0122] Referring to FIG. 3, in the case of the positive electrode for an all-solid-state battery prepared according to Preparation Example 1 of the present invention, it can be seen that a coating layer of a sulfide-based solid electrolyte is uniformly formed on the surface of the positive electrode active material.
[0123] (2) In addition, in the positive electrode for an all-solid-state battery produced according to Production Example 1, an EDX (Energy dispersive X-ray spectroscopy) experiment was carried out to measure the bromine (Br) composition of the first sulfide-based solid electrolyte contained in the positive electrode active material coating layer, and the results are shown in Figure 4. The EDX measurement was carried out using a JEOL JSM7900F.
[0124] As shown in FIG. 4, in the case of the positive electrode for the all-solid-state battery prepared according to Preparation Example 1, it was found that the first sulfide-based solid electrolyte was present in a bromine-rich composition in the coating layer formed on the surface of the positive electrode active material.
[0125] Evaluation example 3: Charge / discharge characteristic analysis The charge / discharge characteristics of each of the all-solid-state batteries of Example 1 and Comparative Examples 1 to 3 were evaluated by the following charge / discharge test.
[0126] The battery was charged at a rate of 0.1 C until the voltage reached 4.25 V (vs. Li), and then cut off at a rate of 0.05 C while maintaining the voltage at 4.25 V (vs. Li). The battery was then discharged at a rate of 0.1 C until the voltage reached 3.0 V (vs. Li) (1 st The results are shown in Figure 5 below.
[0127] Referring to FIG. 5, it was confirmed that the all-solid-state battery according to Example 1 exhibited reversible capacity and energy density at levels almost corresponding to those of the all-solid-state battery according to Comparative Example 1, and exhibited higher reversible capacity and energy density than the all-solid-state batteries according to Comparative Examples 2 and 3.
[0128] Evaluation example 4: High-rate characteristic analysis The all-solid-state batteries of Example 1 and Comparative Examples 1 to 3 were charged and discharged at 0.1 C, 0.2 C, 0.3 C, and 0.5 C in the range of 3.0 to 4.25 V, and the change in discharge capacity depending on each c-rate is shown in FIG.
[0129] Referring to FIG. 6, in the case of the all-solid-state battery according to Example 1, the ion conductivity and the interface characteristics between the active material and the solid electrolyte are improved, and thus the high rate characteristics are improved, as compared with the all-solid-state batteries according to Comparative Examples 1 to 3.
[0130] In particular, it was confirmed that the high rate characteristics of the all-solid-state battery were significantly decreased when a second sulfide-based solid electrolyte not containing bromine was formed in the coating layer of the positive electrode active material and a first sulfide-based solid electrolyte containing bromine was formed in an area other than the positive electrode active material coating layer, i.e., when the first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte were switched in configuration compared to Example 1, the high rate characteristics of the all-solid-state battery were significantly decreased. Therefore, it was found that the high rate characteristics of the all-solid-state battery were improved when a sulfide-based solid electrolyte containing bromine was applied to the positive electrode active material coating layer.
[0131] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the following claims also fall within the scope of the present invention.
Claims
1. A positive electrode for an all-solid-state battery comprising a positive electrode active material, a sulfide-based solid electrolyte, a conductive material, and a binder, The sulfide-based solid electrolyte includes a first sulfide-based solid electrolyte containing a bromine (Br) element and a second sulfide-based solid electrolyte not containing a bromine (Br) element, The positive electrode active material includes a core capable of reversibly absorbing and releasing lithium ions; and a coating layer formed on a surface of the core, The coating layer includes the first sulfide-based solid electrolyte.
2. The positive electrode for an all-solid-state battery according to claim 1 , wherein the first sulfide-based solid electrolyte is represented by the following chemical formula 1: [Chemical formula 1] Li a M 1 b S c X 1 d Br e In the above formula 1, M 1 is Sn, Mg, Ba, B, Al, Ga, In, In, Si, Ge, Pb, N, P, As, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W, or La; 1 is F, Cl, Br, I, Se, Te, or O, and 0<a≦6, 0<b≦6, 0<c≦6, 0≦d≦6, and 0<e≦6.
3. The positive electrode for an all-solid-state battery according to claim 1 , wherein the second sulfide-based solid electrolyte is represented by the following chemical formula 2: [Chemical formula 2] Li k M 2 l S m X 2 n In the above formula 2, M 2 is Sn, Mg, Ba, B, Al, Ga, In, In, Si, Ge, Pb, N, P, As, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W, or La; 2 is F, Cl, I, Se, Te, or O, with 0<k≦6, 0<l≦6, 0<m≦6, and 0≦n≦6.
4. 2. The positive electrode for an all-solid-state battery according to claim 1, wherein the sulfide-based solid electrolyte has an argyrodite-type crystal structure.
5. 2. The positive electrode for an all-solid-state battery according to claim 1, wherein the first sulfide-based solid electrolyte is included in an amount of 5 to 25 parts by weight based on 100 parts by weight of the total of the first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte.
6. The positive electrode of claim 1 , wherein the positive electrode active material is present in an amount of 50 to 95 parts by weight based on 100 parts by weight of the total weight of the positive electrode.
7. 2. The positive electrode of claim 1, wherein the sulfide-based solid electrolyte is present in an amount of 5 to 49 parts by weight based on 100 parts by weight of the total positive electrode.
8. 2. The positive electrode for an all-solid-state battery according to claim 1, wherein the positive electrode active material is coated with 1 to 20 parts by weight of a first sulfide-based solid electrolyte based on 100 parts by weight of a total positive electrode active material including a core and a coating layer.
9. 2. The positive electrode for an all-solid-state battery according to claim 1, wherein the first sulfide-based solid electrolyte has an average particle size of 0.1 μm to 5 μm.
10. The positive electrode for an all-solid-state battery according to claim 1 , wherein the second sulfide-based solid electrolyte has an average particle size of 0.1 μm to 5 μm.
11. 2. The positive electrode of claim 1, wherein the coating layer of the positive electrode active material has a thickness of 0.05 μm to 0.2 μm.
12. 12. An all-solid-state battery comprising: a positive electrode; a negative electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode, the positive electrode comprising the positive electrode according to claim 1.
Citation Information
Patent Citations
Electrolyte-coated positive electrode active material particles, all-solid-state battery, and production method for electrolyte-coated positive electrode active material particles
CN103918110A
Method for manufacturing solid battery
JP2018078076A
Positive electrode for all-solid-state battery, all-solid-state battery, and manufacturing method of positive electrode for all-solid-state battery
JP2022115721A
Composite active material particle, cathode, all-solid-state lithium ion battery, and methods for producing the same
US20220271296A1
Electrolyte-coated positive electrode active material particles, all-solid-state battery, and production method for electrolyte-coated positive electrode active material particles
WO2013073214A1
Cited By
Composite cathode composition based on a sulfide-based solid electrolyte, composite cathodes comprising the same, all-solid-state batteries comprising the same, method for manufacturing the composite cathodes
KR102972776B1
Sulfide-based solid electrolyte-based dry composite cathode sheet, all-solid-state battery comprising the same, composition for dry composite cathode, and method for manufacturing dry composite cathode sheet
KR102988197B1
All-solid-state battery and method for manufacturing all-solid-state battery
WO2026205345A1
